Performance of an Ultra-Sensitive Assay Targeting the Circulating Anodic Antigen (CAA) for Detection of Schistosoma mansoni Infection in a Low Endemic Area in Brazil - Sousa, Mariana Silva; van Dam, Govert J.; Pinheiro, Marta Cristhiany Cunha; de Dood, Claudia J.; Peralta, Jose Mauro; Peralta, Regina Helena Saramago; Daher, Elizabeth de Francesco; Corstjens, Paul L. A. M.; Bezerra, Fernando Schemelzer Moraes (Frontiers in Immunology, 2019)
Techniques with high sensitivity and specificity are required for an accurate diagnosis in low-transmission settings, where the conventional parasitological methods are insensitive. We determined the accuracy of an up-converting phosphor-lateral flow circulating anodic antigen (UCP-LF CAA) assay in urine and serum for Schistosoma mansoni diagnosis in low-prevalence settings in Ceará, Brazil, before and after praziquantel treatment. Clinical samples of a total of 258 individuals were investigated by UCP-LF CAA, point-of-care - circulating cathodic antigen (POC-CCA), soluble worm antigen preparation (SWAP)-ELISA and Kato-Katz (KK); a selection of 128 stools by real-time PCR technique. Three and 6-weeks after treatment, samples were collected and evaluated by detection Schistosoma circulating antigens (CAA and CCA). The UCP-LF CAA assays detected 80 positives (31%) with urine and 82 positives (31.8%) with serum. The urine POC-CCA and serum SWAP-ELISA assays detected 30 (11.6%) and 107 (40.7%) positives, respectively. The Kato-Katz technique revealed only 4 positive stool samples (1.6%). Among the 128 individuals with complete data records, 19 cases were identified by PCR (14.8%); Sensitivities and specificities of the UCP-LF CAA assays, determined versus a combined reference standard based on CCA/KK/PCR positivity, ranged from 60-68% and 68-77%, respectively. In addition only for comparative purposes, sensitivities of the different assays were determined versus a comparative reference based on CAA/KK/PCR positivity, showing the highest sensitivity for the urine CAA assay (80%), followed by the serum CAA (70.9%), SWAP-ELISA (43.6%), PCR (34.5%), POC-CCA (29.1%), whilst triplicate Kato-Katz thick smears had a very low sensitivity (3.6%). CAA concentrations were higher in serum than in urine and were significantly correlated. There was a significant decrease in urine and serum CAA levels 3 and 6-weeks after treatment. The UCP-LF CAA assays revealed 33 and 28 S. mansoni-infected patients at the 3- and 6-week posttreatment follow-up, respectively. The UCP-LF CAA assays show high sensitivity for the diagnosis of S. mansoni in low-endemicity settings. It detects a considerably higher number of infections than microscopy, POC-CCA or PCR. Also it shows to be very useful for evaluating cure rates after treatment. Hence, the UCP-LF CAA assay is a robust and promising diagnostic approach in low-transmission settings.